EVALUASI PELAKSANAAN PROGRAM JAMINAN KESEHATAN DAERAH (JAMKESDA) DI DINAS KESEHATAN KABUPATEN KAYONG UTARA - Hartatik Efendi E.42009071 (FISIP Universitas Tanjungpura Pontianak, 2021)
This Thesis is intended to bring out an evaluation study of the implementation of health programme in order to achieve the level of health is suitable with the goals that want to be attained. This title of this thesis is based on issues raised in the Disrict of North Kayong that there are real people who do not know about the Area Healthy Asurance Program (Jamkesda). This study used a qualitative approach with descriptive research. The research site in the Health Department of North Kayong. The result of the research that has been done shows that there are real people who do not qualify as participants of Jamkesda and lack of socialization by officers to the community and less defly health workers in delivering health service. Others constraints, the problem is the lack of facilities General Hospital as a regional community facilities got better service and more precise. Therefore, it’s need to socialize more often to the community about Jamkesda Programme and the health workers are more expert onto service to the community. Keywords : The Evaluation Program, Area Health Asurance (Jamkesda), Health Care